Relationship between Learning Environment and Academic Achievements: Students perception at Colleges Level - Zeeshan, Muhammad; Fatima, Rameen; Shareef, Areeba (Annals of Human and Social Sciences, 2023)
The learning environment encourages students to develop learning experiences, critical thinking, increases student attention and concentration towards education. Thus, the current study entitled Relationship Between Learning Environment and Academic Achievement: Students' Perception at Colleges Level. The main objective of the study was to highlight the academic achievements of students. A questionnaire was used to obtain the views of the respondents. The document analysis was used to get information about the results of students. The data was analyzed through statistical means through agree percentage, disagree percentage, and One-Way ANOVA. The main conclusions were the first positions of all groups won by the students of colleges from 2017-2019 except one student of higher secondary students stood 1st in the group of Humanities (Male). It was concluded that the overall situation of the infrastructure of colleges in terms of teachers’ ratio per student, classroom per institution, and books per student was better.